AJPEG: A 26.4-pJ/pixel, 252-fps, 128×128 Image Sensor with an In-Sensor Analog DCT Processor for Data Compression - Wan, Rentao; Xu, Yichen; Jee, Dong Woo; Seok, Mingoo (Proceedings of the Custom Integrated Circuits Conference, 2025)
An image sensor is one of the most important building blocks of modern electronics, such as smartphones, drones, and autonomous vehicles. The state-of-the-art image sensor captures an incredibly detailed, high-resolution image [1]-[3], however, it also generates a large amount of data, which overwhelms the downstream processing. To address this challenge, recent works have investigated in- and near-sensor data compression techniques [4]-[14]. [4] is one of the few works which demonstrated the end-to-end systems (containing pixels, compression hardware, and analog-to-digital converters [ADC]). However, it consumes a significant amount of energy of 5919 pJ/pixel, of which the analog discrete cosine transform (DCT) processor takes 58%. On the other hand, [5] proposed the analog compressor and ADC systems (no pixels). However, it also consumes a non-negligible amount of energy (404 pJ/pixel) and exhibits a limited performance of only 6 frame-per-second (fps). In contrast, [6], [7] proposed digital DCT processors, which reduce the energy consumption down to 29-126 pJ/pixel. However, they require the analog-digital conversion of every pixel, which would significantly increase the overall energy consumption.
Keywords: Analog to digital converters; Arts image; Autonomous Vehicles; Building blockes; Discrete cosines; Energy; Energy-consumption; Frames per seconds; Smart phones; State of the art